Cellodextrin Utilization by Bifidobacterium breve UCC2003 - Pokusaeva, Karina; O'Connell-Motherway, Mary; Zomer, Aldert; MacSharry, John; Fitzgerald, Gerald F; van Sinderen, Douwe (Applied and Environmental Microbiology, 2011)
Cellodextrins, the incomplete hydrolysis products from insoluble cellulose, are accessible as a carbon source to certain members of the human gut microbiota, such as Bifidobacterium breve UCC2003. Transcription of the cldEFGC gene cluster of B. breve UCC2003 was shown to be induced upon growth on cellodextrins, implicating this cluster in the metabolism of these sugars. Phenotypic analysis of a B. breve UCC2003::cldE insertion mutant confirmed that the cld gene cluster is exclusively required for cellodextrin utilization by this commensal. Moreover, our results suggest that transcription of the cld cluster is controlled by a LacI-type regulator encoded by cldR, located immediately upstream of cldE. Gel mobility shift assays using purified CldRHis (produced by the incorporation of a His₁₂-encoding sequence into the 3' end of the cldC gene) indicate that the cldEFGC promoter is subject to negative control by CldRHis, which binds to two inverted repeats. Analysis by high-performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD) of medium samples obtained during growth of B. breve UCC2003 on a mixture of cellodextrins revealed its ability to utilize cellobiose, cellotriose, cellotetraose, and cellopentaose, with cellotriose apparently representing the preferred substrate. The cldC gene of the cld operon of B. breve UCC2003 is, to the best of our knowledge, the first described bifidobacterial β-glucosidase exhibiting hydrolytic activity toward various cellodextrins.